Time and cost efficiency analysis of shotcrete and retaining wall methods for landslide disaster mitigation - Muhammad Aulia Rahman; Taufik Dwi (ASEAN Natural Disaster Mitigation and Education Journal, 2026)
Background: The construction industry in Indonesia, particularly in the city of Yogyakarta, is experiencing rapid development along with the increasing demand for educational infrastructure. In projects that involve challenging topographical conditions, the selection of an appropriate earth retaining structure method becomes a critical technical and managerial decision. This study aims to compare the cost and time efficiency between two widely used methods in retaining wall construction, namely the conventional masonry retaining wall method and the shotcrete method, in the Universitas AMIKOM Yogyakarta development project. Methods: The analysis focuses on direct and indirect costs, project duration, productivity, and critical path determination using the Critical Path Method (CPM). Data were obtained from project planning documents, detailed engineering drawings, Bill of Quantities (BoQ), and scheduling data developed using Microsoft Project. Findings: The results of the analysis indicate that the shotcrete method provides significant advantages in terms of time efficiency, with a project duration of approximately 358 working days, which is 42 days faster than the retaining wall method requiring around 400 working days. However, from the cost perspective, the shotcrete method results in higher total expenses, amounting to Rp15.526 billion compared to Rp15.187 billion for the retaining wall method, or approximately 2.24 percent more expensive. Additional analysis of indirect costs shows that the longer duration of the retaining wall method increases monthly overhead expenses, while the shotcrete method requires higher technical and equipment costs. Conclusion: Therefore, the retaining wall method is considered more economical, whereas the shotcrete method is superior when project acceleration is prioritized. The findings of this study provide practical guidance for project managers and decision makers in selecting the most appropriate method based on project objectives, budget limitations, and time constraints. Novelty/Originality of this article: This study uniquely combines cost, time, productivity, and CPM analysis to provide an integrated evaluation of masonry and shotcrete retaining wall methods, offering practical decision-making guidance for complex construction projects.